Economic Viability of Yam Minisett Production and the Problems Affecting Minisett Enterprise in Northern Rivers State, Nigeria - Odinwa, A. B.; Alali, N.; Abali, E. I.; Ahiakwo, A. A; Odinwa, A. N. (Richtmann Publishing, 2011)
This study investigated the economic viability of Yam Minisett Production and the problems affecting minisettenterprise in Ogba/Egbema/Ndoni Local Government Area of Rivers State. A sample size of one hundred (100) respondents,was purposively and randomly selected, and was used for this study. Data collected were analyzed using costs/returns analysisto determine the viability of yam Minisett production and statistical mean derived from Likert rating scale with four options, todetermine the problems associated with yam Minisett production/enterprise in the area. The result, revealed a Net Farm Income(NFI) of (N76, 810.00) and a Gross Margin (GM) or a Return to Management (RM) of N82, 620.00, an indication that yamminisett production is profitable/viable. The result shows that the Gross Margin alone is capable of taking care of another cycle ofproduction of seed yam conveniently without sourcing for extra fund elsewhere. Also shown, was the Return per Naira (R/N)from seed yam production which was put at 0.91, and which means that, from every N1.00 employed in the production of seedyam in the study area, 91k was realized, which is another indication of the viability of seed yam production. Problems identifiedin their order of degrees include: yam minisett production as a micro business for poor people (with weighted mean score =3.38); cost of labour (3.00); lack of awareness of yam Minisett production as an enterprise (2.96); land acquisition problem/soilproblem (2.82); fertilizer unavailability (2.70), etc. Based on the findings, this study recommended among others that: ExtensionAgencies in the area should beef up their awareness strategies in sensitizing the farmers, women and youths inclusive to gobeyond practicing Minisett techniques only to raise seed yams for household use, but should embrace it as a viable business toearn a good living; Also, that Governments/non-governmental organizations should not slack in giving incentives in form ofgrants, subsidies, soft loans and other farm inputs to productive farmers in the area. These incentives should be timely so as toachieve the purpose for which they are given.